A review of animal ethics in tourism: Launching the annals of tourism research curated collection on animal ethics in tourism. (September 2020) - Winter, Caroline
Abstract: A review of research on animal ethics and tourism, based on a sample of 74 articles in ten tourism journals is presented. A range of ethics positions was identified including rights, ecofeminist, ecocentric, welfare, utilitarian, and instrumental. Some studies challenge the ontological bases, and therefore the moral considerability of animals used in tourism: speciesism, native/introduced, a wild-captive continuum and domestic animals. Other themes include the harm caused to animals, and an 'animal gaze' which commodifies animals as objects. The ethical positions of the tourism industry, regulatory groups and tourists were also identified. Overall, the articles challenge the use of animals for entertainment, and confirm the imperative for a developing body of research in the field of animal ethics. Highlights: Reviews the current state of research in animal ethics and tourism in a sample of 74 articles Describes how ethics (instrumentalism, welfare, rights, utilitarianism, ecofeminism and ecocentrism) are used in tourism Identifies an animal ontology that is used to determine animals' moral status, and their touristic use Reviews the research that examines the ethical positions of industry, political and regulatory groups and tourists